Is time to implement a comprehensive corporate governance framework for banks in United Kingdom? - Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Journals of Multidisciplinary Research Academy (IJMRA), 2013)
Corporate governance is part and parcel of banking business activities. The issue of governance can be traced back to the birth of the corporation and many corporate governance guidelines have been introduced to minimize the problems. Among the countries who have introduced corporate governance codes, United Kingdom is the first and earliest country which introduces the corporate governance code and it subsequently improves the code. However, when the UK history of governance issues are examined, the existing code is not able to solve the contemporary governance problems. Among the issues, this paper highlights the existing code is not really comprehensive enough to cover the responsibility of board of directors towards the risk management, transparency of information, competency of directors and role of institutional ownership and reconciliation of stakeholders’ interests. Therefore, this paper suggests there is a need for a more comprehensive corporate governance code in UK.